Antidepressant-Like Effects of Coumaroylspermidine Extract From Safflower Injection Residues - Shifei Li; Ting Li; Yufang Jin; Xuemei Qin; Junsheng Tian; Liwei Zhang (Frontiers Media S.A., 2020)
In this study, a total coumaroylspermidine extract (CSE), which included four coumaroylspermidine compounds, was prepared from safflower injection (a traditional Chinese medicine) residues for the first time. The total content of the four coumaroylspermidine compounds was determined to be 64.86 ± 0.41% using high-performance liquid chromatography. We then evaluated the anti-depressant effect of CSE by using a chronic unpredictable mild stress (CUMS) model in rats. Results of sucrose preference tests, open field tests, and forced swimming tests suggest that CSE exhibits a significant anti-depressant effect. In studies to explore the mechanism, CSE was found to inhibit the increases in levels of corticosterone and decreases in levels of 5-hydroxytryptamine, dopamine, and noradrenaline induced by CUMS. Metabolic profiling showed that 10 endogenous metabolites and four metabolic pathways were altered after CSE treatment. Thus, this study not only found a spermidine extract with antidepressant effect from safflower injection residue for the first time but also provided a way for the efficient utilize of safflower injection residue.